Oil Price Forecasts for the Long-Term: Expert Outlooks, Models, or Both? - Bernard, Jean-Thomas; Khalaf, Lynda; Kichian, Maral; Yelou, Clement (Université d'Ottawa | University of Ottawa, 2015)
Expert outlooks on the future path of oil prices are often relied on by industry participants and policymaking bodies for their forecasting needs. Yet little attention has been paid to the extent to which these are accurate. Using the regular publications by the Energy Information Administration (EIA), we examine the accuracy of annual recursive oil price forecasts generated by the National Energy Modeling System model of the Agency for forecast horizons of up to 15 years. Our results reveal that the EIA model is quite successful at beating the benchmark random walk model, but only at either end of the forecast horizons. We also show that, for the longer horizons, simple econometric forecasting models often produce similar if not better accuracy than the EIA model. Among these, time-varying specifications generally also exhibit stability in their forecast performance. Finally, while combining forecasts does not change the overall patterns, some additional accuracy gains are obtained at intermediate horizons, and in some cases forecast performance stability is also achieved. / Les perspectives d’experts sur la trajectoire future des prix du pétrole sont souvent utilisées par les participants de l’industrie et les entités politiques pour leurs prévisions. Malgré cela, peu de travaux analysent si ces perspectives sont précises. Nous nous basons sur les publications régulières de l’Energy Information Administration (EIA) pour analyser la précision des prévisions annuelles du prix récursif du pétrole générées par le modèle du National Energy Modeling System de l’Agence pour les prévisions avec un horizon jusqu’à 15 ans. Nos résultats révèlent que le modèle EIA est assez performant afin de battre le modèle de marche aléatoire de référence, mais seulement à chaque extrémités des horizons de prévision. Nous montrons également que les modèles simples d’économétrie produisent souvent des résultats similaires sinon meilleurs en précision que le modèle EIA pour les horizons longs. Parmi ceux-ci, les spécifications variant dans le temps produisent également de la stabilité dans leurs performances de prédictions. Finalement, bien que combiner plusieurs prédictions ne change pas les tendances générales, quelques gains de précisions additionnels sont obtenus pour les horizons de temps intermédiaires. Dans certains cas, la stabilité des prédictions de performance est aussi atteinte.
Keywords: Oil price; expert outlooks; long run forecasting; forecast combinations; Prix du pétrole; perspectives d'experts; prévision de long terme; combinaisons de prévision